Еволюційне навчання штучних систем - Tregubenko, I. B. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
The concept of evolutionary learning artificial systems is proposed. A new understanding of the discreteness of the learning process taking into account the principle of limited life cycle artificial systems is formulated. The two-module concept of artificial system modelling, consisted of two interconnecting modules that have different properties and life cycle, is proposed. New concept of B-System is introduced. The artificial systems evolutionary learning task formalization on the base of resource approach is executed. The principles, which allow to technologically simplify the artificial systems learning processes, to decrease the “artificial system – learning environment” pair connections and interaction factors complexity, are formulated.